The basics of prescribing infant formulas - C.J.W. Owens; I.L. Labuschagne; M.J. Lombard (South African Family Practice)
All infant formulas must support the normal growth and development of infants, and this needs to be scientifically demonstrated. Formulas have to contain sufficient amounts of basic nutrients, and so are nutritionally interchangeable, with no evidence indicating that one brand is superior to another.1,2